2016
DOI: 10.15625/1811-4989/14/1/9301
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of GmNAC085 gene under dehydration and salt treatment in drought-tolerant DT51 and drought-sensitive MTD720 soybean cultivars

Abstract: Các yếu tố phiên mã NAC là tác nhân điều hòa quan trọng trong phản ứng của thực vật để đáp ứng với hạn hán và mặn, hai yếu tố stress thẩm thấu ảnh hưởng nhiều nhất tới năng suất cây đậu tương. Trong nghiên cứu trước của chúng tôi, GmNAC085 đã được xác định là gen điều hòa tiềm năng liên quan đến tính chịu hạn ở cả mô rễ và chồi của đậu tương. Trong nghiên cứu này, sự biểu hiện của gen GmNAC085 được tiếp tục đánh giá ở giống đậu tương chịu hạn tốt DT51 và chịu hạn kém MTD720 dưới các điều kiện xử lý stress thẩm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…In our study, we focused on evaluating the effects of GmNAC085 overexpression on several physiological and biochemical traits in soybean plants when they were grown under normal and drought conditions. Expression of GmNAC085 was shown to be induced by dehydration stress in Williams 82 soybean cultivar (Le et al, 2011), DT51 and MTD720 soybean cultivars (Hieu et al, 2016). Meanwhile, another report revealed that the gene activity was also up-regulated in drought-treated soybean plants (Thao et al, 2013;Thu et al, 2014).…”
Section: Introductionmentioning
confidence: 95%
“…In our study, we focused on evaluating the effects of GmNAC085 overexpression on several physiological and biochemical traits in soybean plants when they were grown under normal and drought conditions. Expression of GmNAC085 was shown to be induced by dehydration stress in Williams 82 soybean cultivar (Le et al, 2011), DT51 and MTD720 soybean cultivars (Hieu et al, 2016). Meanwhile, another report revealed that the gene activity was also up-regulated in drought-treated soybean plants (Thao et al, 2013;Thu et al, 2014).…”
Section: Introductionmentioning
confidence: 95%